Estudantes universitários e interrelações com a Teoria das Necessidades de Maslow : significações entre o campo pessoal, acadêmico e profissional - Maihub, Rafael Iassin Abdalla (2023)
Entering academic life creates new perspectives and challenges for students seeking university education. This university stage brings with it meanings from entering the university, and these reflect on the performance of students over the semesters. There are more and more demands for support from university students due to weaknesses and challenges that can be decisive for the success or failure of the student. In this sense, the objective of this work is to investigate how Maslow's theory of the hierarchy of needs interrelates with the difficulties and challenges of university students during their academic career, supported by their confrontations and meanings that permeate their personal, academic and professional field. To investigate the students, an online questionnaire was made available through the Qualtrics platform, which encompassed sociodemographic issues and the different needs of university students: physiological, safety, social, esteem, self-realization, aesthetic and cognitive. A total of 140 students answered the questionnaire, but the number varied between the questions, as it was not mandatory to answer all the questions to move forward. Regarding physiological needs, students understand that food and lack of rest impair academic performance. When analyzing the results, it is noticed that students have a sense of security when they are inside the campus, but not always on the way home. In social needs, family support represents an important factor in their academic lives and in esteem, students feel proud of their achievements during their courses and seek improvement with lectures, seminars and extracurricular activities, which directly affects their needs. cognitive. Students also find the campus an attractive place and feel self-fulfilling upon graduation. The discussion of the results showed that there is a need to look towards welcoming and monitoring those students who, at some point in their academic career, experience certain difficulties and that universities must be prepared to guide these students according to their demands.